Effect of ultrasonic pretreatment on chain elongation of saccharified residue from food waste by anaerobic fermentation. (1st January 2021) - Ma, Hongzhi; Lin, Yujia; Jin, Yong; Gao, Ming; Li, Hongai; Wang, Qunhui; Ge, Shengbo; Cai, Liping; Huang, Zhenhua; Van Le, Quyet; Xia, Changlei
Abstract: Converting biowaste into value-added products has raised the researchers' interests. In this study, bioconversion was applied to produce chain acids from food waste by anaerobic fermentation. To improve the caproic acid production, different pretreatments (i.e., ultrasonic, hydrothermal, and alkaline-thermal) were used for investigating their effects on the acidogenic production and microbial communities. The results showed that ultrasonic and hydrothermal pretreatments (207.8 and 210.1 mg COD/g VS, respectively) were very efficient for enhancing the caproic acid production, compared to the alkaline-thermal pretreated samples and control samples (72.6 and 97.5 mg COD/g VS, respectively). The ultrasonic pretreatment was beneficial for reducing volatile fatty acids (VFAs) during the caproic acid production, resulting in converting more lactic acid to caproic acid by adding the hydrothermal pretreatment. The microbial community analysis showed that the acidogenic bacteria Caproiciproducens dominated the fermentation in this bioconversion process of food waste into chain acids. The Caproiciproducens mainly degraded the proteins and carbohydrates from the saccharified residues of food waste to produce caproic acids through chain elongation procedure. The investigation and optimized method may help develop the bioconversion technology for producing VFAs products from food wastes. Graphical abstract: Image 1 Highlights: Ultrasonic pretreatment promotes chain elongation of the fatty acids during fermentation. Highest caproic acid production exceeded 200 mg COD/g VS by ultrasonic pretreatment. The accumulation of caproic acid was increased by 113% by ultrasonic pretreatment. Caproiciproducen was identified as dominating bacteria for caproic acid production.